THE INFLUENCE OF EDUCATION, TRAINING AND CAREER DEVELOPMENT ON ASN PERFORMANCE - Setiawan, Andi Arif; Hatani, La; Suleman, Nursaban Rommy; Indalestari, Wa Ode Dien; Usman, Usman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine and explain the effect of education, training, and career development on the performance of Civil Servants, both simultaneously and partially. A quantitative approach was employed with data collected cross-sectionally through questionnaires distributed to 37 respondents at the Ministry of Religious Affairs Office in Bombana Regency. The data were analyzed using multivariate regression analysis. The findings reveal that education, training, and career development simultaneously have a positive and significant effect on civil servants’ performance. Partially, each variable also has a positive and significant influence on performance improvement. These results indicate that better implementation of education, training, and career development contributes to higher performance levels among civil servants. Furthermore, respondents’ perceptions support these findings, suggesting that the implementation of education, training, and career development within the organization has been conducted effectively.